Can The Moblees™ Move Canadian Children? Investigating the Impact of a Television Program on Children's Physical Activity - Faulkner, Guy; Bassett-Gunter, Rebecca; White, Lauren; Berry, Tanya R.; Tremblay, Mark S. (Frontiers in Public Health, 2018)
Background: The effects of messaging about physical activity and sedentary behavior purposefully integrated into children's TV programming on children's behavior is unknown. The Moblees is a Canadian childrens' show that explicitly promotes physical activity. Two studies were conducted to (1) examine whether children were more physically active when watching a Moblees episode, and (2) explore parental perceptions of the show. Methods: Study 1 was an experimental study with 21 families randomized to watch an episode of The Moblees vs. a control condition. Movement was assessed through accelerometry and observation. A Chi-square test was used to compare the direct observation proportions of children sitting between intervention and control conditions. Independent t-tests were performed to examine the differences in total vector magnitude counts between the experimental and control groups. Study 2 was an online cross-sectional study with 104 parent/child dyads that included viewing an episode of The Moblees. To identify correlates and predictors of parent-reported child PA during viewing The Moblees compared to other TV programs, Pearson's correlations and a linear regression were calculated, respectively. Results: In study 1 there was a significant association between condition and whether or not children remained sitting χ2 = 55.96, p < 0.001. There was a significant difference in counts between the two conditions, t(13, 61) = 2.29, p < 0.05. Children randomized to the experimental group (i.e., Moblees) moved more compared to control. In study 2 the majority (76%) of parents reported that their child engaged in some physical activity during viewing. Parent encouragement during viewing was the strongest predictor of child physical activity while viewing (β = 0.30, p < 0.01). Conclusion: Television content that includes messaging about physical activity and sedentary behavior, and positive portrayals of physical activity may influence the physical activity of young children. Although the benefits of such modest movement are not clear without further evidence of accumulation over time and/or transfer to other settings, television programming might provide a far reaching medium for knowledge translation.